Asesmen Kualitas RTH Publik Menggunakan Indeks Vegetasi di Taman Hutan Raya Ir. H. Djuanda Kota Bandung - Muhammad Alwan Faris Fadlirullah Raden, Sutadiwangsa; Adytia Heru Nugraha; Ammar Muhammad Nabil; Yulia Asyiawati (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2026)
Urban forest ecosystems are increasingly subject to significant anthropogenic pressures; however, the resulting ecological responses often exhibit a delayed manifestation. The Ir. H. Djuanda Forest Park (Tahura) serves as a vital urban conservation area in Bandung,  Indonesia, which has experienced a massive surge in tourist volume. This study aims to analyze the "lag effect" of visitor pressure on vegetation quality dynamics over the 2015–2025 period. A descriptive quantitative approach was employed, integrating spatial analysis via Google Earth Engine (GEE) to extract Normalized Difference Vegetation Index (NDVI) values from Sentinel-2A satellite imagery. Statistical analyses, including Spearman correlation and linear regression, were conducted with time-lag intervals ranging from 0 to 5 years to identify the relationship between annual visitor numbers and the extent of high-density vegetation. The findings reveal no significant correlation at lag 0 (ρ = –0.12; p > 0.05). Conversely, a significant negative correlation emerged at lag 3 (ρ = –0.61; p < 0.05) and reached its peak at lag 5 (ρ = –0.78; p < 0.01). These results demonstrate a threshold of vegetation resistance, where physical degradation only becomes spectrally manifest after several years of cumulative disturbance. This study recommends the implementation of visitor management policies based on environmental carrying capacity that incorporate temporal variables to ensure the long-term sustainability of the Tahura Ir. H. Djuanda ecosystem.